Development and Validation of a Chromatography Method Using Tandem UV/Charged Aerosol Detector for Simultaneous Determination of Amlodipine Besylate and Olmesartan Medoxomil: Application to Drug-Excipient Compatibility Study - Ariadne M. Brondi; Jerusa S. Garcia; Marcello G. Trevisan (Journal of Analytical Methods in Chemistry)
A study was carried out to investigate compatibility of amlodipine besylate and olmesartan medoxomil with a variety of pharmaceutical excipients. Both drugs are antihypertensive agents that can be administered alone, in monotherapy, or in pharmaceutical association. The studies were performed using binary and ternary mixtures, and samples were stored for 3 and 6 months at 40°C under 75% relative humidity and dry conditions. For this study, a method based on high-performance liquid chromatography (HPLC) was developed and validated for the simultaneous determination of amlodipine besylate and olmesartan medoxomil in samples from pharmaceutical preformulation studies using diode array detector (DAD) and charged aerosol detector (CAD). The runtime per sample was 10 min with retention time of 7.926 min and 4.408 min for amlodipine and olmesartan, respectively. The validation was performed according to ICH guidelines. The calibration curve presents linear dynamic range from 12 to 250 μg mL−1 for amlodipine and from 25 to 500 μg mL−1 for olmesartan with coefficient of determination (R2 ≥ 0.9908) while repeatability and reproducibility (expressed as relative standard deviation) were lower than 1.0%. The excipients such as corn starch, croscarmellose sodium, magnesium stearate, polyvinyl alcohol, talc, polyvinylpyrrolidone, lactose monohydrate, and polyethylene glycol showed potential incompatibilities after accelerated stability testing.